Gene expression in P. falciparum: statistical patterns and molecular determinants - Lemieux, JE (2012)
This thesis investigates patterns and mechanisms of gene expression in P. falciparum. The rapidly cycling patterns of genes during the asexual stages confounds the analysis of gene expression in culture and in patients. In order to overcome this problem, we develop statistical models to estimate the temporal progression of malaria parasites by using the observed gene expression values and known reference sets. We extend this framework to account for lineage commitment, and show that, similar to asexual development, it is also possible to recover information about parasite sexual differentiation given observed gene expression values. Using datasets from our own lab as well as those available in the literature, we establish that the patterns of expression in patients are similar to those observed in culture but in additive mixtures whose proportions can vary between patients. We then investigate epigenetic and spatial factors that are important in regulating gene expression. Using second-generation DNA sequencing, we generate genomic maps of chromatin state and chromosome interactions. These maps provide the first global view of chromosome folding and locus-specific affinities in malaria. They also highlight the importance of epigenetic modifications in imposing structure on the spatial organization of the genome. After generating an initial set of genomic maps, we apply these tools to study chromatin reconfigurations during var gene switching. We show that when the active var gene changes, reconfigurations can be seen in the local three-dimensional chromatin structure of the activated locus. Overall, our results contribute new methods for analyzing malaria microarray data, highlight the importance of lineage mixtures in patient infections, generate an atlas of spatial interactions in the nucleus at a resolution of approximately 5 kilobases, and establish a link in malaria between the spatial configuration of active loci and the local chromatin environment.